Appraisal Methods and Employee Performance in Local Governments: A Case Study of Kibuku District - Mudondo Martina (Uganda Christian University, 2024)
This study examined the relationship between appraisal methods and employee performance within local governments, specifically at Kibuku district Local Government. The research aimed to assess how recognition, promotion, and delegation impacted employee performance among employees. With a population of 40 and a sample size of 36 respondents chosen using the Morgan Table, the study found that recognition positively correlated with employee performance, with 75% of respondents reporting its significant influence, though only 55% felt that current practices were consistent and meaningful. Promotion also affected employee performance, as 60% of respondents indicated that promotions influenced their motivation; however, 50% expressed concerns about fairness and transparency. Delegation showed varied effects, with 65% of employees feeling empowered by delegated tasks, while 40% reported added stress. The study concluded that recognition, promotion, and delegation were crucial for employee performance but needed to be integrated with other factors. It recommended improving recognition practices for consistency, ensuring fairness in promotions, and tailoring delegation strategies to individual needs to enhance overall employee satisfaction.